Kemampuan Spasial Siswa Di Daerah Pedesaan Ditinjau Dari Perbedaan Gender - Erfansyah, Muhammad; Munzir, Said; Johar, Rahmah (Jumper: Journal of Educational Multidisciplinary Research, 2023)
Spatial ability is the ability to imagine, compare, predict, determine, construct, present, and find information from visual stimuli in terms of spatial context that involves manipulation and mental rotation. Students in rural and urban areas have different ways of looking at a problem, especially with regard to spatial. Many opinions state that there are similarities and differences between boys and girls in terms of spatial ability in urban areas, but there is no information about the conditions between male and female students in rural areas. This study aims to describe the spatial ability of junior high school students in rural areas in terms of gender differences. This research is a descriptive research with a qualitative approach. Taking research subjects using snowball sampling technique. The research subjects were six people in one of the junior high schools in Bener Meriah Regency, Aceh Province. Data was collected by means of tests and interviews. Data analysis used qualitative data analysis techniques, namely: data reduction, data presentation, and drawing conclusions. The results showed that the tendency of male students' spatial abilities included five abilities, namely spatial perception, spatial visualization, mental rotation, spatial relations, and spatial orientation, while female students only included four spatial abilities because female students did not meet the mental rotation indicators. In general, both male and female students have difficulty in solving problems related to spatial relations indicators. Therefore, in learning, teachers need to develop students' spatial abilities, especially those related to spatial relations in rural areas, as well as develop abilities with mental rotation indicators, especially for female students.